2006
DOI: 10.1002/bdra.20257
|View full text |Cite
|
Sign up to set email alerts
|

Use of prenatal diagnostic procedures in pregnancies affected with birth defects, Hawaii, 1986–2002

Abstract: Only a fraction of the Hawaii birth defects cases was prenatally diagnosed. The rates for prenatal US, AC/CVS, and prenatal diagnosis among pregnancies affected by birth defects were higher in 1998-2002 than in 1986-1991. AC/CVS rates were lower for maternal age <35 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…In addition, the diagnosis of birth defects may have changed over time. For example, a previous study of Hawaii birth defects registry cases found that the use of prenatal diagnostic procedures and the prenatal diagnosis of birth defects increased in Hawaii during 1986–2002 (Forrester & Merz 2006). Finally, not all families with offspring affected by known or suspected birth defects in Hawaii undergo genetic counseling (Forrester & Merz 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the diagnosis of birth defects may have changed over time. For example, a previous study of Hawaii birth defects registry cases found that the use of prenatal diagnostic procedures and the prenatal diagnosis of birth defects increased in Hawaii during 1986–2002 (Forrester & Merz 2006). Finally, not all families with offspring affected by known or suspected birth defects in Hawaii undergo genetic counseling (Forrester & Merz 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, an anatomic ultrasound is not performed in all women. 48 The availability of anatomic ultrasound is likely to be particularly limited in certain racial/ethnic or low-socioeconomic-status groups. 49 Therefore, although prenatal ultrasound plays an important part in the timely identification of CCHD, population-based data demonstrate that this methodology by itself is insufficient to identify a high proportion of cases.…”
Section: Customary Practicementioning
confidence: 99%
“…In the United States, an anatomic ultrasound is not performed in all women. 48 The availability of anatomic ultrasound is likely to be particularly limited in certain racial/ethnic or lowsocioeconomic-status groups. 49 Therefore, although prenatal ultrasound plays an important part in the timely identification of CCHD, population-based data demonstrate that this methodology by itself is insufficient to identify a high proportion of cases.…”
Section: Customary Practicementioning
confidence: 99%